An experimental investigation of biodiesel steam reforming. (5th January 2015) - Martin, Stefan; Kraaij, Gerard; Ascher, Torsten; Wails, David; Wörner, Antje
Abstract: Recently, liquid biofuels have attracted increasing attention as renewable feedstock for hydrogen production in the transport sector. Since the lack of hydrogen infrastructure and distribution poses an obstacle for the introduction of fuel cell vehicles to the market, it is reasonable to consider using liquid biofuels for on-board or on-site hydrogen generation. Biodiesel offers the advantage of being an environmentally friendly resource while also having high gravimetric and volumetric energy density. The present study constitutes an experimental investigation of biodiesel steam reforming, the main emphasis of which is placed on finding optimum operating conditions in order to avoid catalyst deactivation. Temperature was varied from 600 °C to 800 °C, pressure from 1 bar to 5 bar and the molar steam-to-carbon ratio from 3 to 5. Based on the experimental results, coke formation and sintering are identified as the main deactivation mechanisms. Initiation of catalyst deactivation primarily depends on catalyst inlet temperature and feed mass flow per open area of catalyst. By using a metallic based precious metal catalyst, applying low feed flow rates (31 g/h∙cm 2 ) and a sufficiently high catalyst inlet temperature (>750 °C) coking can be minimized, thus avoiding catalyst deactivation. A stable product gas composition close to chemical equilibrium has been achieved over 100 h with a biodiesel conversion rate of 99%. Highlights: Optimum operating conditions for biodiesel steam reforming are determined. Stable product gas composition was achieved over 100 h of on-stream exposure. Low catalyst inlet temperature and high feed flow rate induce catalyst deactivation.